2021
DOI: 10.3389/fonc.2021.675397
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Cancer-IgG Is Associated With Poor Prognosis and Radioresistance via PI3K/AKT/DNA-PKcs Pathway Regulation in Lung Adenocarcinoma

Abstract: BackgroundLung adenocarcinoma (LUAD) is the dominant type of lung neoplasms, and radiotherapy is its mainstay treatment, yet poor prognosis caused by radioresistance remains problematic. Cancer-derived immunoglobulin G (cancer-IgG) has been detected in multiple cancers and plays important roles in carcinogenesis. This study aimed to demonstrate that cancer-IgG is associated with poor prognosis of LUAD and to identify its role in radioresistance.MethodsCancer-IgG expression was detected by immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Previous researchers have discovered that cancer-IgG is an independent poor (28). Later studies also proved this view and further found that cancer-IgG can also play the role of an oncogene through the AKT, FAK, SOX2, and other signaling pathways in cancer (8,9,19,29). Interacting cells in the TME are considered to regulate the characteristics of cancers, such as uncontrolled proliferation, malignant metastasis, and chemoradiotherapy resistance (30).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous researchers have discovered that cancer-IgG is an independent poor (28). Later studies also proved this view and further found that cancer-IgG can also play the role of an oncogene through the AKT, FAK, SOX2, and other signaling pathways in cancer (8,9,19,29). Interacting cells in the TME are considered to regulate the characteristics of cancers, such as uncontrolled proliferation, malignant metastasis, and chemoradiotherapy resistance (30).…”
Section: Discussionmentioning
confidence: 94%
“…The classical immunological theory holds that immunoglobulin G (IgG), which plays a great role in human defense against pathogenic microorganisms, is produced only by B lymphocytes and plasma cells. However, more and more studies have shown that cancer cells can also produce IgG, called cancer-derived immunoglobulin G (cancer-IgG), such as those in breast cancer, colon cancer, cervical cancer, and lung cancer (6)(7)(8)(9). Lee et al immunized mice with the cleavage product of the ovarian cancer cell line OC-3-VGH to obtain the monoclonal antibody (mAb) RP215, which can specifically recognize cancer-IgG by recognizing a special glycosylation site in the constant region of the IgG heavy chain (10).…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/ AKT/mTOR signaling pathway is hyperactivated or altered in many cancer types (177). Inhibition of the pathway reduces tumor cell radioresistance (178,179). For example, dactolisib, a dual PI3K/ mTOR inhibitor, causes cell cycle arrest in the G2/M phase and improves the radiosensitivity of DU145 cell lines.…”
Section: Pi3k/akt/mtormentioning
confidence: 99%
“…It should be noted that the antigen retrieval solution we used was Tris-EDTA, pH = 8.0. Immunohistochemical scoring criteria can be seen in previous publication from our team [13].…”
Section: Immunohistochemistrymentioning
confidence: 99%